One Size Does Not Fit All: Face Emotion Processing Impairments in Semantic Dementia, Behavioural-Variant Frontotemporal Dementia and Alzheimer’s Disease Are Mediated by Distinct Cognitive Deficits - Laurie A. Miller; Sharpley Hsieh; Suncica Lah; Sharon Savage; John R. Hodges; Olivier Piguet (Behavioural Neurology)
Patients with frontotemporal dementia (both behavioural variant [bvFTD] and semantic dementia [SD]) as well as those with Alzheimer's disease (AD) show deficits on tests of face emotion processing, yet the mechanisms underlying these deficits have rarely been explored. We compared groups of patients with bvFTD (n = 17), SD (n = 12) or AD (n = 20) to an age- and education-matched group of healthy control subjects (n = 36) on three face emotion processing tasks (Ekman 60, Emotion Matching and Emotion Selection) and found that all three patient groups were similarly impaired. Analyses of covariance employed to partial out the influences of language and perceptual impairments, which frequently co-occur in these patients, provided evidence of different underlying cognitive mechanisms. These analyses revealed that language impairments explained the original poor scores obtained by the SD patients on the Ekman 60 and Emotion Selection tasks, which involve verbal labels. Perceptual deficits contributed to Emotion Matching performance in the bvFTD and AD patients. Importantly, all groups remained impaired on one task or more following these analyses, denoting a primary emotion processing disturbance in these dementia syndromes. These findings highlight the multifactorial nature of emotion processing deficits in patients with dementia.